Content Learning System (CLS) Validity and Practicality in Atomic Theory on Project Based Learning (PjBL) with Flipped Classroom For Senior High School In Indonesia - Yulia Asri Warlinda; Kawter Ameen Muhammad Saeed Aledresi; Suryandri Halbi; Cindikia Putri (INTERNATIONAL JOURNAL OF HIGH INFORMATION, COMPUTERIZATION, ENGINEERING AND APPLIED SCIENCE (JHICE), 2021)
With the rapid advancement of technology, it can encourage educators to continue to update the learning media used in transferring knowledge to students. The information re-assets of this have a look at have been three chemistry instructors and college students withinside the town of Padang. The instrument used in the study was a content validity questionnaire and construct validity and a practicality questionnaire. Populations in this research are students from Senior High School in West Sumatera, Indonesia. There are 20 students of SMA N 8 Padang, in X class level as respondents for developing this product. The data analysis technique is to process the numbers that have been obtained from the measurement results of the questionnaire data obtained from calculations using the Aiken's V formula and a Likert scale. The results of the research obtained from the data analysis that have been carried out show that the content of e-learning for the development of atomic theory using the Moodle application produced in this development research has content and construct validity levels of 0.89 and 0.87 with very categories. high and the level of practicality of 0.83 with a very high category. So it can be concluded that the content of e-learning for the development of atomic theory using the Moodle application on the material of atomic theory development is valid and practical.